(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Water management is a multifaceted concept that encompasses the planning, development, distribution, and optimal use of water resources. It is crucial for ensuring the sustainable supply of water for various human needs, including drinking, agriculture, industry, and recreation, while also maintaining the health of aquatic ecosystems. Effective water management involves the integration of scientific, technical, economic, and social considerations to balance competing demands and protect water quality. Legal principles play a pivotal role in guiding water management practices. These principles provide a framework for regulating water use, resolving conflicts, and promoting sustainable practices. Key legal principles in water management include the doctrine of equitable and reasonable use, which ensures fair allocation of water resources among users; the precautionary principle, which mandates proactive measures to prevent water pollution and degradation; and the principle of public participation, which emphasizes the importance of involving stakeholders in decision-making processes. International agreements and national laws often incorporate these principles to address transboundary water issues and domestic water governance. Effective implementation of these legal frameworks requires robust institutional arrangements, transparent governance, and enforcement mechanisms.